Optimization of Audio System Wireles Transmitter Using Green Laser: Nurrisma Puspitasari, Adnan Wahyu Dwiputra, Sudarsono Sudarsono, Gatut Yudoyono, Gontjang Prajitno, Bachtera Indarto - Nurrisma Puspitasari Nurrisma Puspitasari; Adnan Wahyu Dwiputra Adnan Wahyu Dwiputra; Sudarsono Sudarsono; Gatut Yudoyono Gatut Yudoyono; Gontjang Prajitno Gontjang Prajitno; Bachtera Indarto Bachtera Indarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
Nowadays, many activities are done digitally using wireless technology. Wireless technology is the mainstay of communication, but along with the development of the times, there is a wireless technology that utilizes LASER. There has been quite a lot of research on audio systems with wireless transmitters, but none have analyzed the potential of green lasers to obtain the optimal wavelength for communication. This study aims to design a voice transmission system using a laser, determine the relationship between input voltage and laser light intensity, and compare the output frequency with the input frequency. There are three types of measurements: light intensity and distance, laser diode voltage and intensity, and output frequency compared to input frequency. The audio input signal from the source is modulated and transmitted through a laser light medium. The laser beam is then fired into a receiver circuit that can demodulate the signal which is then sent to the output device in the form of a speaker. The study found that the output frequency had the highest error percentage of 38.70% at 125 Hz and the lowest error percentage of 0.07% at 500 Hz when compared to the input frequency. The biggest mistake comes from the volume dropping at a low frequency. The oscilloscope reading is not accurate due to the smaller volume, which leads to a high deviation value and affects the system performance negatively.